2018
DOI: 10.1002/nau.23861
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder in interstitial cystitis/bladder pain syndrome: Relationship to patient phenotype and clinical practice implications

Abstract: Purpose: The relationship between exposure to abuse and interstitial cystitis/bladder pain syndrome (IC/BPS) is well-documented. However, studies have yet to examine posttraumatic stress disorder (PTSD), which develops following exposure to trauma and worsens health outcomes in chronic pain. We aimed to assess the prevalence and impact of PTSD in patients with IC/BPS, including their relation to genitourinary symptom presentation and widespread pain phenotype. Materials and Methods: We recruited 202 particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
1
16
0
3
Order By: Relevance
“…In line with the theoretical model of Yehuda and colleagues, our study provides further evidence that the link between PTSD symptoms and pelvic floor overactivity may particularly be driven by the presence of hypervigilance, which requires high muscle tone (Yehuda et al, 2015). Also in line with the findings of this study, a recent study found that pelvic floor physiotherapy can trigger PTSD symptoms such as nightmares, implying a relation between this specific PTSD symptom and pelvic floor overactivity as well (McKernan et al, 2019). Our findings may be relevant to clinical practice.…”
Section: Discussionsupporting
confidence: 91%
“…In line with the theoretical model of Yehuda and colleagues, our study provides further evidence that the link between PTSD symptoms and pelvic floor overactivity may particularly be driven by the presence of hypervigilance, which requires high muscle tone (Yehuda et al, 2015). Also in line with the findings of this study, a recent study found that pelvic floor physiotherapy can trigger PTSD symptoms such as nightmares, implying a relation between this specific PTSD symptom and pelvic floor overactivity as well (McKernan et al, 2019). Our findings may be relevant to clinical practice.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, the same group reported that the patients who had suffered traumatising childhood events from close others were more likely to have larger bladder capacities (as opposed to that seen in patients with Hunner's lesions) and low affective alexithymia (a key feature of functional somatic syndromes) [53]. In support of this, a recent study of 62 BPS/ IC patients reported that 42% met the diagnostic criteria for post-traumatic stress disorder, with a significantly higher incidence of lifetime sexual abuse and childhood trauma in this group [54]. Identifying these traumatic events as part of a multidisciplinary specialist team approach is therefore essential in order to optimise management of these conditions.…”
Section: Phenotype Based On Psychological Comorbiditymentioning
confidence: 88%
“…There have yet to be any studies exploring an association between domestic abuse with the development of chronic headaches, myofascial pain syndrome, vulvodynia or restless legs syndrome. Although not specific to domestic abuse, recent studies examining other traumatic exposures and psycho‐social co‐morbidities with the development of central sensitization clearly identifies a plausible relationship which requires more investigation due to the largely cross‐sectional nature of existing evidence (McKernan, Johnson, Crofford, et al., 2019; McKernan, Johnson, Reynolds, et al., 2019; McKernan et al., 2018). An approach which overcomes many of the limitations highlighted above, previously adopted by our team, was to use a population‐based dataset to explore the association of domestic abuse with CSS: fibromyalgia, chronic fatigue syndrome and temporomandibular joint disorders using an extract of data which ended in 2017 (Chandan, Thomas, Bradbury‐Jones, Taylor, et al., 2019; Chandan, Thomas, Raza, et al., 2019).…”
Section: Introductionmentioning
confidence: 99%